2001
DOI: 10.1089/109264201750162419
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Cryoablation of a Metastatic Carcinoid Tumor

Abstract: Carcinoid tumors are rare, slow-growing neuroendocrine neoplasms that can cause a carcinoid syndrome. The majority of carcinoid syndromes are the result of multiple hepatic metastases and are usually unresectable. Medical therapy has not proven effective and often causes intolerable side effects. Cryoablation has emerged as a promising treatment for various hepatic lesions when resection is not an option and medical therapy has been exhausted. With the addition of laparoscopy, surgeons now possess a new techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…During freeze/thaw cycles, intracellular and extracellular ice formation occurs in an area termed ‘the iceball’ leading to tumor destruction. Hepatic cryotherapy at laparotomy or laporoscopy surgery for patients with endocrine metastases has been used for a number of years [36, 37, 38, 39, 40, 41, 42]and has demonstrated successful results in terms of symptom control and objective tumor responses [37, 40, 41]. Cryotherapy is a supplement to surgical resection and allows regional destruction of lesions not amenable to resection.…”
Section: Radiofrequency Ablation and Cryotherapymentioning
confidence: 99%
“…During freeze/thaw cycles, intracellular and extracellular ice formation occurs in an area termed ‘the iceball’ leading to tumor destruction. Hepatic cryotherapy at laparotomy or laporoscopy surgery for patients with endocrine metastases has been used for a number of years [36, 37, 38, 39, 40, 41, 42]and has demonstrated successful results in terms of symptom control and objective tumor responses [37, 40, 41]. Cryotherapy is a supplement to surgical resection and allows regional destruction of lesions not amenable to resection.…”
Section: Radiofrequency Ablation and Cryotherapymentioning
confidence: 99%
“…During freeze/thaw cycles, intracellular and extracellular ice formation occurs in an area termed 'the iceball' leading to tumor destruction. Use of hepatic cryotherapy at laparotomy or laporoscopy surgery for patients with endocrine metastases has been used for a number of years (Cozzi et al 1995, Shafir et al 1996, Shapiro et al 1998, Seifert et al 1998, Duperier et al 2001, Sheen et al 2002, Tait et al 2002 and has demonstrated successful results in terms of symptom control and objective tumor responses (Cozzi et al 1995, Shapiro et al 1998, Seifert et al 1998. Cryotherapy is an important supplement to surgical resection and allows regional destruction to lesions not amenable to resection.…”
Section: Cryotherapymentioning
confidence: 99%
“…Cryoablation involves freezing and thawing of tumors, resulting in tumor ablation. [55][56][57][58][59] Cryotherapy can be used percutaneously or intraoperatively using intraoperative ultrasound and probes, and has become an important adjunct to surgical cytoreduction. Drawbacks include the large size of the probe, which causes increased risk for hemorrhage and higher rates of complications for larger metastases.…”
Section: Cryoablationmentioning
confidence: 99%